Peningkatan Kompetensi Masyarakat Nelayan Juwana Melalui Basic Safety Training (BST) - Sugeng Haryadi; K Kundori (LPPM STIKOM Tunas Bangsa, 2022)
The incidence of fishing vessel accidents is a very complex problem, namely in the form of human factors caused by the captain and crew, engine factors in the form of ships and safety equipment, and natural factors in the form of weather and utilization of fishery resources. The method used in this training activity is through an outreach approach and the delivery of further material by practicing the use of safety equipment on board. The counseling strategy can be done by means of lectures, and practicum activities where participants are taught to practice how to use the safety equipment on board, namely life-saving appliances in the form of life jackets, lifebuoys, thermal protective aids, other methods used are discussed or question and answer. This community service activity uses qualitative and quantitative approaches. The management used is by identifying, planning, organizing, and acting. The planning and organizing stages are carried out so that activities run on the target, effectively, and efficiently, the next stage is implementation and action in the field in the form of safety education for fishermen. the impact of the activity is evaluated during and after the implementation of the activity. The description of the impact of the activity is descriptive qualitative in the form of things that can be seen and felt by all parties involved in the activity. Basic Safety Training (BST) training activities have been carried out and run smoothly both from the process of delivering materials, training processes, discussion, and evaluation processes. The fishing community can understand various types of safety equipment and the importance of using safety equipment in accordance with the explanation from the speaker so that it is expected to be applied when working on fishing boats. The need for further training related to basic safety training (BST) regarding the introduction and use of fire extinguishers